Are commonly used paediatric reference intervals for water and electrolyte balance appropriate for clinical use?. (January 2015) - Dodd, Alan; El-Farhan, Nadia; Moat, Stuart
Background: Paediatric reference intervals are less well characterized than in adults. An initiative for harmonization of pathology across the United Kingdom has recommended an interval for sodium of 133–146 mmol/L at all ages. Methods: To assess the validity of this, the laboratory database was interrogated for all renal profiles (sodium, potassium, urea and creatinine) for children presenting to primary care over a 13-year period. While the primary interest was in sodium results, sufficient current data were also available for potassium and creatinine and so these were included for study. The electrolyte results were filtered to include only normal renal function and the remaining data were analysed for age-related differences. Results: Sodium concentrations were observed to be lower for infants (1–5 years of age) with a mean of 138 mmol/L, increasing towards adult concentrations (mean 140 mmol/L) by teenage years. A similar pattern was seen for potassium results, and creatinine was seen to increase with age. At all ages, the distributions of sodium concentrations measured in this population were observably tighter than the interval of 133–146 mmol/L recommended by Pathology Harmony. Conclusions: We suggest that this interval is too wide, and more work is needed to establish more appropriate paediatric ranges.